POLITIK MASKULIITAS DAN BAHASA SEKSIS: BAPAKISME RIDWAN KAMIL DALAM AKUN INSTAGRAM @RIDWANKAMIL - Bintang Purwaramdhona, Ananda; Adji, Muhamad; Prabasmoro, Tisna (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
The New Order's masculinity politics, which perpetuates hegemonic masculinity through the concept of bapakism, is still influential after the reform. The implications can be seen from the dominance of the